Administration of Sex Hormone Preparations as a Risk Factor in the Development of Intrahepatic Cholestasis of Pregnancy and Biliary Sludge in Pregnant Women - Yu. B. Uspenskaya; I. V. Kuznetsova; A. A. Sheptulin; N. V. Goncharenko; A. N. Gerasimov; M. M. Amiraslanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Sex hormone preparations are widely used in obstetrics for the treatment of infertility and miscarriage. Possible adverse effect of sex hormone preparations during pregnancy is their potential adverse impact on the hepatobiliary system. The most common pathology of the liver and gallbladder associated with pregnancy are intrahepatic cholestasis of pregnancy (ICP) and biliary sludge (BS).Aim.  The aim of the study is to evaluate the effect of female sex hormones on the course and effectiveness of treatment of ICP and BS during pregnancy. Materials and methods.  The study included 158 pregnant women (97 patients with ICP and 61 patients with BS). Exogenous hormonal effects were the use of assisted reproductive technologies (ARTs) and in vitro fertilization (IVF) for the onset of conception and/or the use of estrogen and progesterone preparations during pregnancy. ICP was diagnosed on the basis of detection of an elevated level of bile acids (above 8 μmol/L) in the blood serum. Patients underwent clinical, laboratory and instrumental studies (abdominal ultrasound, including the assessment of gallbladder motor-evacuator function initially and after 2 months of treatment, and pelvic ultrasound). Pruritus intensity associated with ICP was assessed using a 0–3 score scale. Patients with BS received treatment with ursodeoxycholic acid (UDCA) in a dose of 250–750 mg and choleretic herbal preparation (artichoke extract) for 2 months. Patients with ICP were treated with UDCA in a dose of 500–2000 mg until delivery. Biochemical laboratory parameters in the ICP group were evaluated after 1 and 2 weeks of treatment.Results.  More than half of patients with BS and ICP were taking sex hormone preparations or had a pregnancy that occurred after the application of ART programs. In patients who became pregnant after ART, the ICP developed at a significantly earlier time than in patients with a naturally occurring pregnancy (p < 0.001). The use of sex hormones proved to be interrelated with a high frequency of cholestasis recurrence after its regression in the course of the treatment (p < 0.001). Patients with pregnancy after ART programs, as well as taking sex hormones, had an increased risk of BS developement. The intake of sex hormones (p = 0.005) in patients with ICP was associated with a more frequent development of preeclampsia and the need for caesarean section (p = 0.003). The use of ART programs and hormonal therapy, as well as the presence of BS in patients with ICP, were interrelated with oxidative stress. BS on the ICP background was associated with the development of intrauterine fetal hypoxia. In pregnant women with BS, the reception of progestins was significantly (p = 0.004) correlated with functional impairment of the motor function of the biliary tract (BT). In the presence of BS, ICP occurs with more severe liver damage, and the patients are inferior to respond to UDCA treatment. Prognostic factors in the insufficient effectiveness of BS treatment: the use of sex hormone preparations during pregnancy, the presence of the polycystic ovary syndrome (PCOS) in the anamnesis, an older age at the time of pregnancy and conception after ART.Conclusion. The use of sex hormone preparations and ART programs are shown to be additional factors contributing to the emergence of ICP and BS during pregnancy. For the pregnant women taking sex hormone preparations and/or becoming pregnant after ART programs, it is important to conduct laboratory and ultrasound screening for early detection and timely treatment of ICP and BS. BC patients of older ages who have become pregnant after ART programs and take sex hormones preparations and/or have a PCOS in an anamnesis may need longer or repeated courses of BS treatment.